Catalyst for selective hydrogenation of phenylacetylene in presence of styrene and preparation method thereof
By using alumina support and hydrothermal reaction nano-blade Ni-Zn catalyst prepared in the presence of styrene, the problems of low hydrogenation rate of phenylacetylene and high styrene loss rate in the prior art were solved, and high activity and Highly selective hydrogenation has excellent application prospects.
Patent Information
- Application Number
- CN202310695279.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-13
AI Technical Summary
In the presence of styrene, the hydrogenation rate of phenylacetylene is low and the styrene loss rate is high, making it difficult to achieve both high activity and high selectivity.
Alumina is used as a support to form a nano-blade-like Ni-Zn catalyst with regular surface morphology through hydrothermal reaction, which is used for selective hydrogenation of carbon eight fractions, reduce the agglomeration of Ni metal particles, improve the dispersion of active components, and pass Zn acts as a selective promoter to improve styrene selectivity.
The stability and selective hydrogenation of the catalyst at high temperatures are achieved, the hydrogenation loss of phenylacetylene is reduced, the selectivity of styrene is improved, and the hydrogenation activity is significantly improved, with practical application prospects.
Smart Images

Figure CN119158578A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of C8 hydrogenation catalysts, and in particular to a catalyst for selective hydrogenation of phenylacetylene in the presence of styrene and a preparation method thereof. Background Art
[0002] Styrene (ST) is an important monomer for the production of polystyrene, ABS resin, styrene-butadiene rubber, etc. Ethylbenzene dehydrogenation is the main preparation method, but it has the disadvantage of high production cost. In recent years, with the large-scale production of ethylene, the extraction of styrene from the carbon eight fraction produced as a by-product of ethylene cracking has become an attractive new way to increase styrene production.
[0003] Taking a 1000kt / a ethylene unit as an example, about 20 to 40kt of styrene can be obtained annually, and mixed xylene can be recycled, so that the cracked C8 fraction is upgraded from fuel value to chemical value. At the same time, due to the separation of the C8 fraction, the load of the subsequent hydrogenation unit of the pyrolysis gasoline is reduced, the hydrogen consumption is reduced, and the poisoning of the pyrolysis gasoline hydrogenation catalyst caused by styrene polymerization is avoided.
[0004] The current method for recovering styrene from pyrolysis gasoline is extractive distillation. However, this part of the pyrolysis C8 fraction contains 4000-15000 μg·g -1 Phenylacetylene (PA), while ST and PA have similar chemical structures, and the interactions between the two and the extractive distillation solvents are also similar. Therefore, the effective separation of ST and PA cannot be achieved through the existing extractive distillation process conditions. The presence of these phenylacetylenes will not only increase the catalyst consumption during the anionic polymerization of styrene, but also affect the chain length and polymerization rate, and will affect the color, odor and comprehensive performance of the polymerization product. Therefore, before extracting styrene from the carbon eight fraction of ethylene cracking, phenylacetylene must be selectively hydrogenated. The carbon eight fraction contains 25-45% styrene. Therefore, when hydrogenating phenylacetylene, it is also necessary to minimize the hydrogenation loss of styrene. The phenylacetylene content and styrene loss in the hydrogenated product determine the benefits of the process for recovering styrene from the carbon eight fraction of cracked gasoline.
[0005] At present, more than 80% of the styrene selective hydrogenation catalysts that have been industrially applied in domestic styrene extraction units use nickel-based catalysts. The preparation method adopts the conventional equal volume impregnation method. Before use, it is generally necessary to perform high-temperature activation in flowing hydrogen to reduce NiO to metal Ni particles, which may cause agglomeration and sintering of Ni particles, resulting in poor stability and selectivity. Therefore, researchers have improved the selective hydrogenation performance of supported Ni-based catalysts by adding additives and improving the preparation method. To solve this problem, existing patents and literature reports that on the one hand, the purpose of adjusting the interaction between the carrier and the active component is achieved by modifying the carrier; on the other hand, the selective hydrogenation performance of the catalyst is improved by adding additives such as Zn, Cu, Mg, Co or Sn to adjust the geometry and electronic structure of the Ni active site. Although it has a certain effect on improving the selectivity of styrene, there is still room for improvement, and it is difficult to achieve both high activity and high selectivity.
[0006] For example, Chinese patent document CN107952446A discloses a nickel catalyst for selective hydrogenation of phenylacetylene in a C8 fraction, which comprises the following components, measured by weight percentage: (a) 5 to 30% of metallic nickel or its oxide; (b) 0.01 to 20% of at least one element selected from molybdenum or tungsten or its oxide; (c) 0.01 to 10.0% of at least one element selected from rare earths or its oxide; (d) 0.01 to 2.0% of at least one element selected from IA or IA in the periodic table or its oxide; (e) 0 to 15% of at least one element selected from silicon, phosphorus, boron or fluorine or its oxide; (f) 0 to 10% of at least one element selected from IVB in the periodic table or its oxide; and (g) the balance of aluminum oxide.
[0007] Chinese patent document CN102649066A discloses a catalyst for selective hydrogenation of phenylacetylene in the presence of styrene, which comprises the following components by weight percentage: 2 to 50.0% of metallic nickel or its oxide; 0.05 to 10% of at least one element selected from rare earth or its oxide; 40 to 88% of a carrier, the carrier is selected from at least one of aluminum oxide, silicon oxide or molecular sieve, and the specific surface area of the carrier is 60 to 300 m 2 / g.
[0008] Chinese patent document CN102649065A relates to a catalyst for selective hydrogenation of phenylacetylene in the presence of styrene, comprising the following components by weight percentage: (a) 2 to 50 parts of metallic nickel or its oxide; (b) 0.05 to 10 parts of at least one element selected from rare earths or its oxide; (c) 0.01 to 5 parts of at least one element selected from IA and IIA in the periodic table or its oxide; (d) 49 to 85 parts of a carrier; wherein the carrier is selected from alumina, the average pore diameter of the carrier is 3 to 30 nm, the pore volume is 0.4 to 1.5 ml / g, and the specific surface area is 100 to 450 m2 / g, and the technical solution can be used in the industrial production of hydrogenation to remove phenylacetylene in the presence of styrene.
[0009] Chinese patent document CN107413344A discloses a method for preparing a nano nickel-based catalyst with a confined structure and hexahedral morphology. First, a nickel-aluminum hydrotalcite precursor with an organic carbon chain intercalation is synthesized, and a confined nickel-based catalyst is prepared by explosive in-situ uniform reduction of an organic carbon source. The catalyst structure is characterized by high crystallinity, small-sized hexahedral metal nickel nanoparticles confined on Ni(Al)Ox / C.
[0010] Chinese patent document CN114249300A provides an application of a specific microstructured alumina-supported Ni catalyst in plasma-catalyzed methane dry reforming to produce synthesis gas. Methane and carbon dioxide are used as raw materials, Ni / Al2O3 is used as a catalyst, and a reaction is carried out in a plasma reactor to prepare synthesis gas under mild conditions; Al2O3 is a mixture of one or more of nano-sheet Al2O3, feather-like Al2O3, ball-shaped Al2O3, and rod-shaped Al2O3 with different microstructures. The above-mentioned different structural carriers directly affect the dispersion, stability and discharge capacitance of Ni particles, thereby affecting the catalytic performance of Ni / Al2O3 under mild conditions.
[0011] Chinese patent document CN112705209A provides a reforming hydrogen production catalyst and its preparation method and application. The catalyst includes the following components by mass: 3-10% nickel, 50-60% magnesium, 0.6-0.7% lanthanum, and the rest oxygen; the sum of the mass percentages of the above elements is 100%. The catalyst is prepared by hydrothermal method and coprecipitation method. Nickel and magnesium form Ni x Mg y O solid solution has very excellent anti-sintering and anti-carbon deposition properties; on this basis, through the modification of trace lanthanum elements, it shows good catalytic activity in a low temperature environment.
[0012] Chinese patent document CN108212134A discloses a silicon-containing boehmite catalyst carrier and a preparation method thereof. The catalyst carrier is a porous material, the porous material is a porous silicon-aluminum material, the porous silicon-aluminum is in the form of nanosheets, the silicon oxide content is 1-20wt%, and the specific surface area is 800-1000m 2 / g, pore volume is 1.7-4.0cm 3 / g, and the most probable pore size is 2-30nm. This solution controls the reaction endpoint by adjusting the mass ratio of sodium aluminate, aluminum sulfate and water glass according to the content of aluminum oxide and silicon oxide, and can prepare a nano-sheet-shaped silicon-containing boehmite catalyst carrier with a large specific surface area and a large pore volume, that is, the carrier has a nano-sheet structure.
[0013] Chinese patent document CN102649063A discloses a catalyst for the selective hydrogenation of phenylacetylene in the presence of styrene, which comprises the following components by weight percentage: (a) 2 to 50.0% of metallic nickel or its oxide; (b) 0.05 to 10% of at least one element selected from rare earths or its oxide; (c) 0.01 to 6% of at least one element selected from IB, IIB, VIB or VIIB in the periodic table or its oxide; (d) 49 to 85% of a carrier. The technical solution in which the carrier is selected from a composite carrier of aluminum oxide and silicon oxide, and the weight ratio of aluminum oxide to silicon oxide is 0.01 to 100:1, can be used in the industrial production of hydrogenation to remove phenylacetylene in the presence of styrene. Although this solution improves the activity and selectivity of the selective hydrogenation of phenylacetylene in the presence of styrene, the addition of silicon oxide will inevitably affect the acidity of the carrier, thereby affecting the operating stability of the catalyst.
[0014] Chinese patent document CN1160284C discloses a method for hydrogenating phenylacetylene in a styrene-containing medium with the aid of a catalyst, wherein the catalyst is a nickel catalyst supported on a carrier material with a nickel content of 10-25 wt %, and the hydrogen / phenylacetylene molar ratio is 1-10. Summary of the invention
[0015] In view of the problems existing in the prior art and the directions for improvement, the present invention provides a catalyst for the selective hydrogenation of phenylacetylene in the presence of styrene to solve the technical problems of low phenylacetylene hydrogenation rate and high styrene loss rate (i.e., high activity and high selectivity cannot be achieved at the same time) in the selective hydrogenation process of phenylacetylene in the presence of styrene in the prior art.
[0016] To achieve the above object, the present invention provides a catalyst for the selective hydrogenation of phenylacetylene in the presence of styrene, wherein the carrier is alumina, and the catalyst for the selective hydrogenation of phenylacetylene is a Ni-Zn catalyst with a nano-leaf structure having a regular surface morphology;
[0017] Among them, the average thickness of the leaves is 5-20nm, the average width of the leaves is 300-3000nm, the average length of the leaves is 300-3000nm, and the specific surface area is 70-240m 2 / g, pore volume is 0.25~0.60cm 3 / g.
[0018] In the above-mentioned phenylacetylene selective hydrogenation catalyst provided by the present invention, the alumina carrier is not specifically limited, and commercially available alumina can be used or it can be prepared by an existing preparation method. For example, the nitric acid method, the sulfuric acid method, the carbon dioxide method or other existing methods are all possible. Specifically, after kneading alumina powder and water, it is extruded into strips, or rolled into a sphere, dried at 80-120°C, and roasted at 800-1100°C for 4-6 hours; and the alumina prepared by the existing preparation method may contain a small amount of conventionally doped silicon oxide, titanium oxide, zirconium oxide, etc., but the content will not exceed 5wt%, which will not affect the implementation of this scheme.
[0019] Optionally, the catalyst for selective hydrogenation of phenylacetylene in the presence of styrene provided by the present invention has an average blade thickness of 8 to 15 nm, an average blade width of 500 to 1500 nm, an average blade length of 500 to 1500 nm, and a specific surface area of 90 to 160 m 2 / g, pore volume is 0.35~0.50cm 3 / g.
[0020] Optionally, based on the total mass of the phenylacetylene selective hydrogenation catalyst as 100%, the Ni content is 8wt% to 18wt%, preferably 10wt% to 15wt%; the Zn content is 0.5wt% to 4wt%, preferably 1wt% to 2wt%.
[0021] The present invention also provides a method for preparing the above-mentioned phenylacetylene selective hydrogenation catalyst in the presence of styrene, comprising the following steps:
[0022] 1) impregnating an alumina carrier in a nickel salt aqueous solution, drying and calcining to obtain a semi-finished catalyst; the nickel in the semi-finished catalyst accounts for 70 wt% to 95 wt% of the nickel in the phenylacetylene selective hydrogenation catalyst;
[0023] 2) dissolving nickel salt and zinc salt in a mixed solution of alcohol and water, then adding the semi-finished catalyst, stirring evenly, washing, drying and calcining the solid obtained by hydrothermal reaction to obtain the catalyst for selective hydrogenation of phenylacetylene in the presence of styrene.
[0024] Optionally, in the method for preparing the catalyst for selective hydrogenation of phenylacetylene in the presence of styrene provided by the present invention, the volume ratio of alcohol to water in the mixed solution of alcohol and water is 4 to 1:1, preferably 2 to 1:1; the alcohol is at least one of methanol, anhydrous ethanol and propanol, preferably anhydrous ethanol.
[0025] Optionally, in the method for preparing the catalyst for selective hydrogenation of phenylacetylene in the presence of styrene provided by the present invention, the zinc salt is a soluble zinc salt, preferably at least one of zinc nitrate, zinc chloride, zinc fluoroborate and zinc sulfate, more preferably zinc nitrate; the nickel salt is selected from at least one of nickel sulfate, nickel nitrate, nickel chloride and nickel acetate, preferably nickel nitrate and / or nickel acetate.
[0026] Optionally, in the preparation method of the catalyst for selective hydrogenation of phenylacetylene in the presence of styrene provided by the present invention, the process conditions of the hydrothermal reaction can be conventional in the industry, such as the parameters disclosed in (Contemporary Petrochemical Industry, 2015, 9: 16-22). The temperature of the hydrothermal reaction recommended by the present invention is 100-250°C and the time is 2-48h; preferably, the temperature of the hydrothermal reaction is 120-200°C and the time is 4-24h.
[0027] Optionally, in the preparation method of the catalyst for selective hydrogenation of phenylacetylene in the presence of styrene provided by the present invention, the parameters for drying and calcining in step 1) and step 2) are not specifically limited, and conventional parameters in the industry can be adopted. The present invention recommends that the drying temperature is 80 to 150° C., the calcining temperature is 300 to 500° C., and the calcining time is 2 to 8 hours.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The catalyst for selective hydrogenation of phenylacetylene in the presence of styrene provided by the present invention uses alumina as a carrier and forms a Ni-Zn catalyst with a regular nanosheet morphology on its surface through a hydrothermal reaction. When the catalyst is used for selective hydrogenation of carbon eight fraction to remove phenylacetylene, it has the advantage of not being easy to agglomerate after high-temperature reduction and has excellent hydrogenation selectivity.
[0030] 2. The catalyst for selective hydrogenation of phenylacetylene in the presence of styrene provided by the present invention has a surface nano-flake morphology that can not only effectively prevent the aggregation of Ni metal particles during high-temperature calcination and improve the dispersion of active components, and weaken the strong interaction between Ni and alumina, but also the active site isolation effect uses Zn as a selective promoter to improve styrene selectivity, thereby showing high activity and high selectivity in the selective hydrogenation reaction of phenylacetylene, and has practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1This is a SEM image of the catalyst obtained in Example 1 of the present invention;
[0032] Figure 2 This is a SEM image of the catalyst prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0034] Example 1
[0035] This embodiment provides a phenylacetylene selective hydrogenation catalyst, and the preparation method thereof is as follows:
[0036] (1) dissolving nickel nitrate in deionized water to prepare an impregnation solution, then placing a carrier alumina into the impregnation solution for impregnation, drying the impregnated carrier at 110° C. for 4 hours, and calcining at 380° C. for 4 hours to obtain a semi-finished catalyst; wherein the nickel in the semi-finished catalyst accounts for 85% of the total mass of the nickel in the phenylacetylene selective hydrogenation catalyst;
[0037] (2) Nickel nitrate and zinc nitrate were dissolved in 70 mL of a mixed solution of methanol and water (volume ratio of methanol to water: 7:3), and then the semi-finished catalyst was added and stirred evenly. The mixture was then transferred to a high-pressure hydrothermal synthesis reactor and kept at 150° C. for 12 h. After naturally cooling to room temperature, the sample was dried at 90° C. for 6 h and calcined at 500° C. for 4 h to obtain a catalyst. Based on the total mass of the catalyst as 100%, the Ni content in the catalyst was 12 wt% and the Zn content was 1.5 wt%.
[0038] The above catalyst was scanned by electron microscope. Figure 1 As shown in the figure, its surface is nanosheet-like, with an average blade thickness of 10 nm, an average blade width of 598 nm, and an average length of 397 nm. The specific surface area of the catalyst is 105 m 2 / g, pore volume is 0.41cm 3 / g.
[0039] Example 2
[0040] This embodiment provides a phenylacetylene selective hydrogenation catalyst, and the preparation method thereof is as follows:
[0041] (1) dissolving nickel chloride in deionized water to prepare an impregnation solution, then placing a carrier alumina into the impregnation solution for impregnation, drying the impregnated carrier at 120° C. for 3 h, and calcining at 350° C. for 4.5 h to obtain a semi-finished catalyst; wherein the nickel in the semi-finished catalyst accounts for 70% of the total mass of the nickel in the phenylacetylene selective hydrogenation catalyst;
[0042] (2) Nickel nitrate and zinc sulfate were dissolved in 80 mL of a mixed solution of anhydrous ethanol and water (the volume ratio of anhydrous ethanol to water was 3:2), and then the semi-finished catalyst was added and stirred evenly. The mixture was then transferred to a high-pressure hydrothermal synthesis reactor and kept at 160° C. for 9 h. After naturally cooling to room temperature, the sample was dried at 130° C. for 3 h and calcined at 340° C. for 6 h to obtain a catalyst. Based on the total mass of the catalyst being 100%, the Ni content in the catalyst was 13.8 wt% and the Zn content was 0.8 wt%.
[0043] Scanning the catalyst under an electron microscope revealed that the surface was in the form of nanosheets, with an average blade thickness of 12 nm, an average blade width of 760 nm, and an average length of 412 nm. The specific surface area of the catalyst was 167 m 2 / g, pore volume is 0.55cm 3 / g.
[0044] Example 3
[0045] This embodiment provides a phenylacetylene selective hydrogenation catalyst, and the preparation method thereof is as follows:
[0046] (1) dissolving nickel nitrate in deionized water to prepare an impregnation solution, then placing a carrier alumina into the impregnation solution for impregnation, drying the impregnated carrier at 130° C. for 2.5 hours, and calcining at 330° C. for 5 hours to obtain a semi-finished catalyst; wherein the nickel in the semi-finished catalyst accounts for 75% of the total mass of the nickel in the phenylacetylene selective hydrogenation catalyst;
[0047] (2) Nickel nitrate and zinc chloride were dissolved in 75 mL of a mixed solution of anhydrous ethanol and water (the volume ratio of anhydrous ethanol to water was 1:1), and then the above-mentioned semi-finished catalyst was added and stirred evenly, and then transferred to a high-pressure hydrothermal synthesis reactor and maintained at 170° C. for 7 hours. After naturally cooling to room temperature, the sample was dried at 90° C. for 8 hours and calcined at 350° C. for 4 hours to obtain a catalyst. Based on the total mass of the catalyst as 100%, the Ni content in the catalyst was 12.5wt% and the Zn content was 1.5wt%.
[0048] Scanning the catalyst under an electron microscope revealed that the surface was in the form of nanosheets, with an average blade thickness of 14 nm, a blade width of 974 nm, and a length of 816 nm. The specific surface area of the catalyst was 119 m 2 / g, pore volume is 0.43cm 3 / g.
[0049] Example 4
[0050] This embodiment provides a phenylacetylene selective hydrogenation catalyst, and the preparation method thereof is as follows:
[0051] (1) dissolving nickel nitrate in deionized water to prepare an impregnation solution, then placing a carrier alumina into the impregnation solution for impregnation, drying the impregnated carrier at 140° C. for 2 hours, and calcining at 310° C. for 6 hours to obtain a semi-finished catalyst; wherein the nickel in the semi-finished catalyst accounts for 80% of the total mass of the nickel in the phenylacetylene selective hydrogenation catalyst;
[0052] (2) Nickel nitrate and zinc fluoroborate were dissolved in 68 mL of a mixed solution of propanol and water (volume ratio of propanol to water: 4:1), and then the semi-finished catalyst was added and stirred evenly. The mixture was then transferred to a high-pressure hydrothermal synthesis reactor and kept at 170° C. for 7 h. After naturally cooling to room temperature, the sample was dried at 140° C. for 2 h and calcined at 320° C. for 7 h to obtain a catalyst. Based on the total mass of the catalyst as 100%, the Ni content in the catalyst was 14 wt % and the Zn content was 0.5 wt %.
[0053] Scanning the catalyst under an electron microscope revealed that the surface was in the form of nanosheets, with an average blade thickness of 7 nm, a blade width of 485 nm, and a length of 325 nm. The specific surface area of the catalyst was 101 m 2 / g, pore volume is 0.39cm 3 / g.
[0054] Example 5
[0055] This embodiment provides a phenylacetylene selective hydrogenation catalyst, and the preparation method thereof is as follows:
[0056] (1) dissolving nickel acetate in deionized water to prepare an impregnation solution, then placing a carrier alumina into the impregnation solution for impregnation, drying the impregnated carrier at 100° C. for 5 hours, and calcining at 360° C. for 4.5 hours to obtain a semi-finished catalyst; wherein the nickel in the semi-finished catalyst accounts for 90% of the total mass of the nickel in the phenylacetylene selective hydrogenation catalyst;
[0057] (2) Nickel nitrate and zinc nitrate were dissolved in 77 mL of a mixed solution of anhydrous ethanol and water (the volume ratio of anhydrous ethanol to water was 3:1), and then the semi-finished catalyst was added and stirred evenly. The mixture was then transferred to a high-pressure hydrothermal synthesis reactor and kept at 190° C. for 3 h. After naturally cooling to room temperature, the sample was dried at 110° C. for 5 h and calcined at 400° C. for 4 h to obtain a catalyst. Based on the total mass of the catalyst being 100%, the Ni content in the catalyst was 11.5 wt% and the Zn content was 2 wt%.
[0058] The catalyst C1 was scanned by electron microscope, and its surface was nanosheet-like, with an average blade thickness of 15nm, an average blade width of 1437nm, and an average length of 1192nm. The specific surface area of the catalyst C1 was 132m 2 / g, pore volume is 0.47cm 3 / g.
[0059] Example 6
[0060] This embodiment provides a phenylacetylene selective hydrogenation catalyst, and the preparation method thereof is as follows:
[0061] (1) dissolving nickel acetate in deionized water to prepare an impregnation solution, then placing a carrier alumina into the impregnation solution for impregnation, drying the impregnated carrier at 110° C. for 3.5 hours, and then calcining at 450° C. for 3 hours to obtain a semi-finished catalyst; wherein the nickel in the semi-finished catalyst accounts for 95% of the total mass of the nickel in the phenylacetylene selective hydrogenation catalyst;
[0062] (2) Nickel nitrate and zinc fluoroborate were dissolved in 65 mL of a mixed solution of propanol and water (the volume ratio of anhydrous ethanol to water was 2:1), and then the semi-finished catalyst was added and stirred evenly. The mixture was then transferred to a high-pressure hydrothermal synthesis reactor and kept at 140° C. for 18 h. After naturally cooling to room temperature, the sample was dried at 100° C. for 6 h and calcined at 450° C. for 3 h to obtain a catalyst. Based on the total mass of the catalyst being 100%, the Ni content in the catalyst was 10 wt % and the Zn content was 3 wt %.
[0063] Scanning the catalyst under an electron microscope revealed that the surface was in the form of nanosheets, with an average blade thickness of 17 nm, an average blade width of 1671 nm, and an average length of 1254 nm. The specific surface area of the catalyst was 89 m 2 / g, pore volume is 0.35cm 3 / g.
[0064] Comparative Example 1
[0065] This comparative example provides a phenylacetylene selective hydrogenation catalyst, and its preparation method is as follows:
[0066] Weigh 20 grams of a composite carrier with a weight ratio of aluminum oxide to silicon oxide of 20:1, add it to a mixed solution of nickel nitrate, lanthanum nitrate and zinc nitrate, and impregnate it by equal amount impregnation method. Dry it at 120°C for 6 hours and calcine it at 400°C for 8 hours to obtain a nickel-based catalyst with a nickel content of 12% of the weight of the carrier, a lanthanum content of 0.8% and a zinc content of 1.5%.
[0067] The catalyst was scanned by electron microscope. Figure 2 As shown by Figure 2It can be seen that the catalyst surface exists in the form of irregular spherical aggregates, which are prone to agglomeration during high-temperature reduction or long-term evaluation.
[0068] Comparative Example 2
[0069] This comparative example provides a phenylacetylene selective hydrogenation catalyst, and its preparation method is as follows:
[0070] Nickel nitrate and zinc chloride were dissolved in water to prepare an impregnation solution, and then the carrier alumina was placed in the impregnation solution and impregnated by equal volume impregnation method. The impregnated carrier was dried at 130°C for 2.5 hours and then calcined at 330°C for 5 hours to obtain a catalyst. The total mass of the catalyst was 100%, and the Ni content of the catalyst was 12.5wt%, and the Zn content was 1.5wt%. The specific surface area of the catalyst was 107m 2 / g, pore volume is 0.41cm 3 / g.
[0071] Comparative Example 3
[0072] This comparative example provides a phenylacetylene selective hydrogenation catalyst, and its preparation method is as follows:
[0073] 7.5g aluminum nitrate and 6g urea were added to 70mL deionized water and stirred magnetically for 20 minutes to obtain a colorless and transparent solution. The solution was then transferred to a high-pressure reactor, hydrogen was introduced to expel the air in the reactor, and then the hydrogen pressure of the reactor was set to 0.5MPa, and the reactor was sealed. The reactor was heated to 120°C and reacted for 24 hours. After the reaction was completed, the reactor was cooled naturally to room temperature, the gas in the reactor was discharged, the reactor was opened, and the reaction slurry was collected. The reaction slurry was filtered, and the filtrate was washed with deionized water for 3 times, and then the filtrate was transferred to an 80°C oven and dried for 8 hours to obtain a γ-alumina precursor-monohydrate soft stone. Finally, the monohydrate soft stone was placed in a muffle furnace for calcination, and the temperature was raised from room temperature to 550°C at 2°C / min, and it was kept for 6 hours and then naturally cooled to obtain blade-shaped nano γ-alumina. The specific surface area of the obtained γ-alumina is 267m 2 / g, and the average pore size is 6.7nm.
[0074] Then, nickel acetate and zinc nitrate were dissolved in deionized water to prepare an impregnation solution, and then the blade-shaped nano-γ-alumina carrier was put into the impregnation solution. After the impregnation, the blade-shaped nano-γ-alumina carrier was dried at 110° C. for 5 hours, and then calcined at 360° C. for 4.5 hours to obtain a catalyst. Based on the total mass of the catalyst being 100%, the Ni content in the catalyst was 11.5wt%, and the Zn content was 2%.
[0075] Comparative Example 4
[0076] This comparative example provides a phenylacetylene selective hydrogenation catalyst, and its preparation method is as follows:
[0077] Nickel nitrate and zinc fluoroborate were dissolved in water to prepare an impregnation solution, and then the carrier alumina was placed in the impregnation solution and impregnated by equal volume impregnation method. The impregnated carrier was dried at 110°C for 3.5 hours and calcined at 450°C for 3 hours to obtain a catalyst. The total mass of the catalyst was 100%, and the Ni content of the catalyst was 10wt%, and the Zn content was 3%. The specific surface area of the catalyst was 85m 2 / g, pore volume is 0.33cm 3 / g.
[0078] Catalytic performance evaluation
[0079] Raw material composition and analysis method:
[0080] The main components of the raw materials are: 35wt% of styrene (ST for short) and 0.5wt% of phenylacetylene (PA for short).
[0081] Raw materials and product composition: The raw materials and composition were analyzed using Agilent 7890B gas chromatograph.
[0082] Catalyst evaluation conditions: After the catalyst was reduced at 350°C for 12h in a hydrogen atmosphere, an adiabatic bed reactor was used with a reaction temperature of 28°C, a reaction pressure of 0.3MPa, a H2 / PA molar ratio of 3.5:1, and a liquid hourly space velocity of 1.5h -1 , catalyst loading amount is 150ml.
[0083] Reaction process flow: The C8 fraction is measured by a metering tube and then raised to the reaction pressure by a plunger pump. After preheating, it is mixed with the hydrogen at a constant pressure and enters the catalyst bed from the bottom of the reactor. The reaction product is cooled and then enters the gas-liquid separator for separation. The separated H2 is decompressed and measured by a wet flow meter and then vented. The liquid is discharged into the product storage tank, and the content of ST, PA and other components therein is analyzed using an Agilent 7890B gas chromatograph.
[0084] The evaluation conditions and results of the catalysts prepared in the specific examples and comparative examples are shown in Table 1.
[0085] Table 1 Evaluation conditions and results of examples and comparative examples
[0086]
[0087]
[0088] From the data in the above table, it can be seen that the phenylacetylene selective hydrogenation catalyst provided by the present invention has excellent hydrogenation activity and selectivity in the presence of styrene, with high PA hydrogenation rate and low ST loss. However, the selectivity of the catalyst prepared by the existing impregnation method for phenylacetylene is significantly reduced.
[0089] The above embodiments are typical examples listed to illustrate the technical solutions of the present invention in detail. The present invention is subject to the protection scope of the claims and the content of the invention and is not limited by the implementation scheme. Simple replacement or modification of the present invention is still within the protection scope of the present invention.
Claims
1. A catalyst for the selective hydrogenation of phenylacetylene in the presence of styrene, wherein the carrier is alumina. It is characterized in that The phenylacetylene selective hydrogenation catalyst is a Ni-Zn catalyst with a nano-leaf structure with regular surface morphology; Among them, the average thickness of the leaves is 5-20nm, the average width of the leaves is 300-3000nm, the average length of the leaves is 300-3000nm, and the specific surface area is 70-240m 2 / g, pore volume is 0.25~0.60cm 3 / g.
2. A catalyst for the selective hydrogenation of phenylacetylene in the presence of styrene as claimed in claim 1, It is characterized in that The average leaf thickness is 8-15 nm, the average leaf width is 500-1500 nm, the average leaf length is 500-1500 nm, and the specific surface area is 90-160 m 2 / g, pore volume is 0.35~0.50cm 3 / g.
3. A catalyst for selective hydrogenation of phenylacetylene in the presence of styrene as claimed in claim 1, It is characterized in that Based on the total mass of the phenylacetylene selective hydrogenation catalyst as 100%, the Ni content is 8wt% to 18wt%, preferably 10wt% to 15wt%; the Zn content is 0.5wt% to 4wt%, preferably 1wt% to 2wt%.
4. A method for preparing a catalyst for selective hydrogenation of phenylacetylene in the presence of styrene according to any one of claims 1 to 3, It is characterized in that The steps include: 1) impregnating an alumina carrier in a nickel salt aqueous solution, drying and calcining to obtain a semi-finished catalyst; the nickel in the semi-finished catalyst accounts for 70 wt% to 95 wt% of the nickel in the phenylacetylene selective hydrogenation catalyst; 2) dissolving nickel salt and zinc salt in a mixed solution of alcohol and water, then adding the semi-finished catalyst, stirring evenly, washing, drying and calcining the solid obtained by hydrothermal reaction to obtain the catalyst for selective hydrogenation of phenylacetylene in the presence of styrene.
5. The preparation method according to claim 4, It is characterized in that In the alcohol-water mixed solution, the volume ratio of alcohol to water is 4-1:1, preferably 2-1:1; the alcohol is at least one of methanol, anhydrous ethanol and propanol, preferably anhydrous ethanol.
6. The preparation method according to claim 4, It is characterized in that The zinc salt is a soluble zinc salt, preferably at least one of zinc nitrate, zinc chloride, zinc fluoroborate and zinc sulfate; the nickel salt is selected from at least one of nickel sulfate, nickel nitrate, nickel chloride and nickel acetate, preferably nickel nitrate and / or nickel acetate.
7. The preparation method according to claim 4, It is characterized in that The temperature of the hydrothermal reaction is 100-250° C., and the time is 2-48 hours; preferably, the temperature of the hydrothermal reaction is 120-200° C., and the time is 4-24 hours.
8. The preparation method according to claim 4, It is characterized in that The drying temperature is 80-150° C., the calcining temperature is 300-500° C., and the calcining time is 2-8 hours.
Citation Information
Patent Citations
Catalyst for selective hydrogenation of phenylacetylene in presence of styrene
CN102649065A
Method for removing phenylacetylene through selective hydrogenation under existence of styrene
CN108863700A
Preparation method of catalyst for preparing styrene through selective hydrogenation of phenylacetylene
CN115124402A
Supported high dispersion nickel-based alloy catalyst preparation method and catalytic application thereof
WO2016078261A1
Selective hydrogenation method for alkyne in c2 fraction
WO2021073640A1
